2014
DOI: 10.1186/1471-2474-15-206
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive plate osteosynthesis with a locking compression plate is superior to open reduction and internal fixation in the management of the proximal humerus fractures

Abstract: BackgroundThe use of minimally invasive plate osteosynthesis (MIPO) via anterolateral deltoid splitting has good outcomes in the management of proximal humerus fractures. While using this approach has several advantages, including minimal soft tissue disruption, preservation of natural biology and minimal blood loss, there is an increased risk for axillary nerve damage. This study compared the advantages and clinical and radiological outcomes of MIPO or open reduction and internal fixation (ORIF) in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 39 publications
6
52
0
1
Order By: Relevance
“…Our results of the functional scores are comparable with those presented in earlier studies [15,20,22,37,38], that there were no differences between open deltopectoral reduction and fixation vs. a minimally-invasive deltoid-splitting approach. Complications were comparable with other studies in type and number [15,38,39].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results of the functional scores are comparable with those presented in earlier studies [15,20,22,37,38], that there were no differences between open deltopectoral reduction and fixation vs. a minimally-invasive deltoid-splitting approach. Complications were comparable with other studies in type and number [15,38,39].…”
Section: Discussionsupporting
confidence: 94%
“…Complications were comparable with other studies in type and number [15,38,39]. Hepp et al [20] and Lin et al [22] found differences in the sub-scores of the CS in a short term follow-up at three months postoperatively which we could not confirm. In our study we focused on the long-term results which are more relevant to influence patients' satisfaction and outcome.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…10,12,16,23,30 In recent years, however, more and more surgeons have realized that conventional fixation methods might be the key reason for increasing complications observed in patients with fracture. 2,13 Therefore, the biological osteosynthesis concept has been developed to draw more attention to soft tissue circumstances. 17,26 In addition, numerous MIPO techniques have been designed aiming to preserve soft tissue and the periosteum blood supply at the fracture site, including femoral, tibial, and humeral shaft fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al 25) carried out a plate fixation of displaced proximal humeral fractures in a total of 86 patients. In 43 patients, they carried out a standard delto-pectoral approach and in the other 43 patients, a deltoid-splitting approach.…”
Section: Discussionmentioning
confidence: 99%